Working with Practicing Teachers in a High-Stakes Teaching Context to Rethink their Pedagogical Practices with Children of Diverse Backgrounds. (2nd July 2016) - Brown, Christopher P.; Weber, Natalie Babiak
ABSTRACT: The public education system in the United States continues to struggle in educating children of diverse backgrounds. Many have addressed this issue by documenting how certain practices teach children particular types of knowledge and skills. This developmental focus on what should be happening to children of diverse backgrounds tends to ignore the complexities of the communities in which they live, and by doing so, it can perpetuate the status quo. To address this issue, this article examined a professional development course within a large urban school district for preKindergarten and Kindergarten teachers. In the course, the teachers were asked to reconceptualize their pedagogical practices with their students and engage in learning activities in their classrooms that attended to the children's sociocultural worlds. Analyzing the experiences of a sample of participants who participated in this course provides insight into how teacher educators can assist practicing and preservice teachers address the opportunities and challenges that exist when teaching children of diverse backgrounds through culturally relevant practices that prepare them for success in their high-stakes schooling environments and local communities.